PENGARUH UKURAN PERUSAHAAN, TIPE INDUSTRI, GROWTH, DAN MEDIA EXPOSURE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2015) - Widiastuti, Harjanti; Utami, Evy Rahman; Handoko, Ridi (Universitas Muhammadiyah Surakarta, 2018)
This research aimed to analyze the influence of size, type of industry, growth, and media exposure on Corporate Social Responsibility Disclosure. The samples of this research are companies that has been listed in the Indonesia Stock Exchange between 2014 and 2015. Data in this study were obtained from annual reports and online newspapers. Regression analysis will be employed to answer the research question. The result showed that size and type of industry positively and significantly infuenced Corporate Social Responsibility (CSR) Disclosure. Growth negatively infuenced Corporate Social Responsibility (CSR) Disclosure dan media exposure has no influence on Corporate Social Responsibility (CSR). Keywords: Corporate Social Responsibility Disclosure, size, type of industry, growth, and media exposure.